Linearly polarized ytterbium laser enabled by an antiresonant hollow-core fiber inline polarizer - Goel, Charu (2022)
We report a linearly polarized ytterbium-doped fiber (YDF) laser cavity configured by integrating an antiresonant hollow-core fiber-based inline polarizer. The 5-cm-long compact fiber polarizer was fusion spliced to a commercial large-mode-area, polarization-maintaining YDF. Near-diffraction-limited linearly polarized signal output with a polarization extinction ratio of > 21 dB was achieved for up to 25 W of power that was limited only by the available pump power. The performance of the hollow-core fiber polarizer was found to be temperature insensitive, which obviates the need for the precise temperature control required in all-fiber, high-power polarized laser cavities employing crossed fiber Bragg gratings. We used the tapering technique to scale down the geometry of the polarizing fiber and shift its operating wavelength by ∼100 nm, which makes it an attractive candidate for a variety of fiber laser applications.